2015
DOI: 10.3389/fgene.2015.00210
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping of tuberculosis and pigmentation-related traits in an African–European hybrid cattle population

Abstract: Admixture mapping affords a powerful approach to genetic mapping of complex traits and may be particularly suited to investigation in cattle where many breeds and populations are hybrids of the two divergent ancestral genomes, derived from Bos taurus and Bos indicus. Here we design a minimal genome wide SNP panel for tracking ancestry in recent hybrids of Holstein–Friesian and local Arsi zebu in a field sample from a region of high bovine tuberculosis (BTB) endemicity in the central Ethiopian highlands. We fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
0
15
3
1
Order By: Relevance
“…The present study did not confirm QTL identified in previous association studies on bTB susceptibility [1721], which further supports the notion of a polygenic trait controlled by multiple genes. The closest GWA results on BTA 23 were reported by Richardson et al [18] who identified a QTL about 28 Mb downstream on the same chromosome for Irish dairy cattle.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The present study did not confirm QTL identified in previous association studies on bTB susceptibility [1721], which further supports the notion of a polygenic trait controlled by multiple genes. The closest GWA results on BTA 23 were reported by Richardson et al [18] who identified a QTL about 28 Mb downstream on the same chromosome for Irish dairy cattle.…”
Section: Discussioncontrasting
confidence: 91%
“…Tsairidou et al [20] applied RHM to perform a meta-analysis using the datasets from previous studies in the Republic of Ireland [17] and Northern Ireland [19], and identified a new region on BTA 6. Furthermore, Kassahun et al [21] also identified a SNP on BTA 6 associated with bTB in a mixed breed cattle population in Ethiopia; however, this region was distinct from that of Tsairidou et al [20]. In general, genomic studies performed to date have not revealed any major common QTL; therefore further studies with independent populations are required.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate that some of the breeds studied have distinct genetic profiles (e.g., Kholmogory, Yakut, Yaroslavl) making them priority targets for deeper studies to reveal signatures of selection and adaptations related to local environments and for conservation purposes. We also observed that a large group of breeds had both old and recent influence from commercial European breeds (e.g., Kostroma, Kazakh Whiteheaded, Istoben) meaning that their genomes could potentially contain only a small fraction of ancestral alleles, but these could be important for surviving local conditions and can be used for admixture mapping programs aiming at economically important traits (Kassahun et al 2015). The links between the Russian breeds and breeds from other countries presented in this study form a basis for future work on contrasting their genomes to reveal causative alleles or haplotypes using a right set of related and outgroup populations for the comparison to avoid 'signal dilution' or false positive signals.…”
Section: Discussionmentioning
confidence: 83%
“…Although the reasons for low across-study consistency are likely manifold and include different criteria to classify phenotypes and different statistical procedures, these results suggest that loci with a major effect on Johne's disease do not exist, at least in these breeds. Likewise, GWASs for susceptibility to bovine tuberculosis (caused by Mycobacterium bovis) yielded inconsistent results (Bermingham et al, 2014;Finlay et al, 2012;Kassahun et al, 2015;Richardson et al, 2016). Efforts to identify susceptibility alleles for other infectious diseases detected small-effect loci with poor replicability (reviewed in (Raszek et al, 2016)).…”
Section: Gwass In Cattle and Swinementioning
confidence: 99%